In-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material and preparation method thereof
By constructing core-shell-type bio-based flame-retardant nanoparticles in situ in epoxy resin, the problems of low fracture toughness, poor impact resistance and flammability in actual applications of epoxy resin materials are solved, and the excellent flame-retardant performance of the material is achieved. and impact resistance.
Patent Information
- Application Number
- CN202211631385.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-19
AI Technical Summary
In actual applications, existing epoxy resin materials have problems such as low fracture toughness, poor impact resistance, flammability and inability to self-extinguish without fire, which limits their wide application in some fields.
By constructing core-shell bio-based flame-retardant nanoparticles in situ in epoxy resin, epoxy vegetable oil reaction is used to synthesize phosphazepyphene epoxy vegetable oil intermediates, and core-shell bio-baseds are constructed through non-hydrolyzed sol-gel reaction. The flame-retardant nanoparticles allow the nanoparticles to be evenly and stably dispersed in the epoxy resin.
It achieves excellent flame retardant and impact resistance of epoxy resin materials, with high toughness and strength, significantly improving the overall performance of the material.
Smart Images

Figure 221219145925 
Figure 221219145931 
Figure 221219145938
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material and a preparation method thereof. Background Art
[0002] Epoxy resin is widely used in the fields of electronics and electrical industry due to its high tensile strength and modulus, low curing shrinkage, high adhesion, good chemical corrosion resistance and excellent dimensional stability. However, due to the high crosslinking density of epoxy resin, it has low fracture toughness and poor impact resistance in practical applications, and is flammable and cannot self-extinguish when away from fire, which limits its wide application in certain fields. Therefore, how to perform flame retardant modification and toughening modification on epoxy resin to obtain high-performance epoxy resin with excellent comprehensive performance has always been the research focus and difficulty in the field.
[0003] A large number of studies have shown that adding organic-inorganic nanoparticles, especially core-shell nanoparticles, to epoxy resin can achieve a balance between toughness, strength and modulus of epoxy composites. Silica nanoparticles are the world's largest, non-toxic and inexpensive nanofillers, and have been used in the application research of strengthening and toughening a variety of resins. However, in the existing studies on nanoparticle (including core-shell nanoparticle) modified epoxy composites, nanoparticles are added by physical blending or solution blending to prepare nanocomposites. Due to the large specific surface area of nanoparticles, they are easy to agglomerate to form stress concentration points, resulting in a decrease in material strength and toughness. Although surface treatment and modification can improve the dispersion or interfacial effect of nanoparticles in the polymer matrix, many studies have found that after nanoparticles are grafted onto polymers, more obvious multi-particle aggregation occurs, and this aggregation state is difficult to separate by strong mechanical force. In addition, in the preparation of nanocomposites by physical blending, the addition of nanoparticles often leads to an increase in the viscosity of the composite resin system, which reduces its processing performance to a certain extent, and is not conducive to the single and uniform dispersion of nanoparticles, resulting in limited performance improvement. In the solution blending method, nanoparticles need solvent-assisted dispersion before adding epoxy resin. During the molding process, the volatilization of the solvent will cause environmental pollution and may also introduce defects due to residual solvent.
[0004] Adding flame retardants is an effective solution to quickly improve the flame retardant properties of epoxy resin and meet the flame retardant requirements of materials. Phosphorus-based flame retardants degrade to phosphoric acid or polyphosphoric acid when burned at high temperatures, which easily form high-viscosity molten glass and a dense carbonized layer on the surface of the burning material, isolating the inner matrix of the material from heat and oxygen, resulting in less smoke and toxic gas release and high flame retardant efficiency. However, most existing phosphorus-containing flame retardants are non-reactive flame retardants. Due to the weak interface between the flame retardant and the epoxy resin matrix, the compatibility is poor, which will lead to the deterioration of the mechanical properties of the material.
[0005] Under the general trend of the development of halogen-free organophosphorus flame retardants, phosphaphenanthrene flame retardants have received much attention in the research of flame retardant modification of epoxy resin due to their higher thermal stability and more efficient flame retardant effect. Fan Juanjuan and others from the School of Huaxue and Materials Science of Guizhou Normal University used 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) as the main raw material, and synthesized a phosphaphenanthrene-based high-efficiency flame retardant 10-(2,5-dihydroxydiphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-sulfide (DOPS-NQ) through a two-step reaction, and used it for flame retardant modification of epoxy resin; the research results show that DOPS-NQ needs to be compounded with ammonium polyphosphate (APP) in a certain proportion to obtain a better flame retardant effect, while APP has poor compatibility with epoxy resin matrix, and some APP agglomerates in the substrate to cause stress concentration, which reduces the mechanical properties of the material. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, the present invention aims to provide an in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material having both excellent flame retardancy and impact resistance.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for preparing an in-situ core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material comprises the following steps:
[0010] (1) The epoxy vegetable oil and DOPO are heated to 120-160°C under an inert gas atmosphere and reacted for 24-48 hours to synthesize a phosphaphenanthrene epoxy vegetable oil intermediate; wherein the mass ratio of the epoxy vegetable oil to DOPO is 1:(0.2-1.2);
[0011] (2) dissolving the phosphaphenanthrene epoxy vegetable oil intermediate in an organic solvent, adding a silane coupling agent, reacting for 1-5 hours under the protection of an inert gas atmosphere, removing the solvent after the reaction is completed, drying, and obtaining a phosphaphenanthrene siloxane bio-based macromolecule; the silane coupling agent is selected from any one or more of an aminosilane coupling agent or an isocyanate silane coupling agent; when the silane coupling agent is selected from an aminosilane coupling agent, the mass ratio of the phosphaphenanthrene epoxy vegetable oil intermediate to the aminosilane coupling agent is 1: (0.05-0.5), and the reaction temperature is 80-100°C; when the silane coupling agent is selected from an isocyanate silane coupling agent, the mass ratio of the phosphaphenanthrene epoxy vegetable oil intermediate to the isocyanate silane coupling agent is 1: (0.2-0.6), and the reaction temperature is 0-100°C;
[0012] (3) The phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, initiator and epoxy resin are mixed evenly in a mass ratio of (1-10):(1-10):(1.5-15):(0.01-0.15):100, and a non-hydrolytic sol-gel reaction is carried out at a temperature of 80-100°C for 1-5 hours, and an in-situ polycondensation is performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture.
[0013] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and the curing agent are mixed in a mass ratio of 100:(20-50) and stirred evenly, and then vacuum degassed at 20-40°C, poured into a mold and cured to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material.
[0014] The DOPO described in the present invention is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0015] The epoxidized vegetable oil is preferably selected from any one or more of epoxidized soybean oil, epoxidized castor oil or epoxidized linseed oil.
[0016] The aminosilane coupling agent is preferably selected from any one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane or aminoethylaminoethylaminopropyltrimethoxysilane.
[0017] The isocyanate silane coupling agent is preferably selected from any one or more of isocyanate propyl trimethoxy silane, isocyanate propyl triethoxy silane, isocyanate propyl methyl dimethoxy silane or isocyanate propyl methyl diethoxy silane.
[0018] The inert gas is preferably nitrogen, helium or argon.
[0019] The organic solvent is preferably selected from one or more of tetrahydrofuran, 1,4-dioxane, diglyme, chloroform, ethanol, petroleum ether or n-hexane. Further preferably, the mass ratio of the phosphaphenanthrene epoxy vegetable oil intermediate to the organic solvent is 1:(5-10).
[0020] The epoxy resin is preferably selected from any one or more of epoxy resin E51, epoxy resin E44, epoxy resin E42 or epoxy resin E31.
[0021] The initiator is preferably selected from any one or more of barium hydroxide and dibutyltin dilaurate.
[0022] The curing agent is preferably selected from any one or more of diaminodiphenylmethane, diaminodiphenylaldehyde, polyetheramine, amino-terminated trimethylolpropane tripropylene glycol ether, hexahydrophthalic anhydride or tetrahydrophthalic anhydride.
[0023] Preferably, the average epoxy value of the phosphaphenanthrene epoxy vegetable oil intermediate is 0.04 mol / 100 g to 0.42 mol / 100 g. The average epoxy value is measured according to the national standard GB / T 1677-1981 Determination of epoxy value of plasticizers (hydrochloric acid-acetone method).
[0024] Preferably, the average molecular weight of the phosphaphenanthrene siloxane bio-based macromolecule is 1000-7500 g / mol; more preferably 1500-5500 g / mol. If the molecular weight is too large, adding it to the epoxy resin will have a greater impact on the mechanical properties, resulting in a decrease in impact properties and elongation at break. The present invention can obtain the phosphaphenanthrene siloxane bio-based macromolecule of the required molecular weight by controlling the mass ratio of the phosphaphenanthrene epoxy vegetable oil intermediate and the silane coupling agent. The average molecular weight is measured according to the national standard GB / T 21864-2008 standard method for detecting the average molecular weight and molecular weight distribution of polystyrene (high performance size exclusion chromatography).
[0025] The average particle size of the core-shell bio-based flame-retardant nanoparticles in the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material of the present invention is 0.1nm-100nm, the core diameter is 10-100nm; the shell thickness is ≤50nm. The average particle size is tested according to the standard GB / T 29022 particle size analysis dynamic light scattering (DLS) particle size analysis; the core diameter and shell thickness are measured according to transmission electron microscopy observation.
[0026] The weight content of the core-shell bio-based flame-retardant nanoparticles in the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material of the present invention is 1%-20%. The present invention can control the content of the core-shell bio-based flame-retardant nanoparticles in the composite material by controlling the addition amount of phosphaphenanthrenesiloxane bio-based macromolecules, trimethyloxyphenylsilane and dihydroxydiphenylsiloxane. The content of the core-shell bio-based flame-retardant nanoparticles is within the required range, which is conducive to ensuring the rigidity and toughness of the material. Too high a content increases the defects of the material and causes the material to have a decreased impact resistance.
[0027] The present invention also provides an application of the above-mentioned in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material, which can be specifically used in the field of high-temperature structural flame-retardant materials such as aerospace, electronics and electrical, and power energy.
[0028] The present invention has the following beneficial effects:
[0029] The present invention utilizes epoxy vegetable oil to react with DOPO and an aminosiloxane coupling agent, and simultaneously introduces flame retardant primitives phosphaphenanthrene and siloxane structure into the molecular structure of the epoxy vegetable oil, and in situ constructs and generates core-shell bio-based flame retardant nanoparticles with a "hard core" of a polysilsesquioxane-like structure and a "soft shell" of a phosphaphenanthrene epoxy branched macromolecular enriched layer in an epoxy resin precursor through a non-hydrolytic sol-gel method, so that the nanoparticles can be uniformly and stably dispersed in the epoxy resin group, and the "soft shell" phosphaphenanthrene epoxy branched macromolecular enriched layer effectively increases the compatibility of the nanoparticle surface with the epoxy resin matrix, which can greatly improve the toughness and strength of the material, and at the same time, the flame retardant property of the material is significantly improved through phosphorus-silicon synergistic flame retardancy, thereby obtaining an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material with both excellent flame retardant property and impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the phosphaphenanthrenesiloxane bio-based macromolecule of Example 1.
[0031] Figure 2 This is the nuclear magnetic resonance phosphorus spectrum of the phosphaphenanthrenesiloxane bio-based macromolecule of Example 1.
[0032] Figure 3 This is a particle size distribution diagram of the core-shell bio-based flame retardant nanoparticles of the in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material of Example 1.
[0033] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of the phosphaphenanthrenesiloxane bio-based macromolecule of Example 8.
[0034] Figure 5This is a cross-sectional microscopic morphology of the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material of Example 10. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0036] The reagents and raw materials used in the examples and comparative examples of the present invention are all commercially available.
[0037] Example 1
[0038] (1) Under the protection of high-purity nitrogen, DOPO and epoxidized soybean oil ESO (the mass ratio of epoxidized soybean oil to DOPO was 1:1) were added to a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 150°C for 72 h to obtain a phosphaphenanthrene epoxidized soybean oil intermediate with an average epoxide value of 0.07 mol / 100 g.
[0039] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy soybean oil intermediate was dissolved in 1,4-dioxane (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to 1,4-dioxane was 1:5), γ-aminopropyltriethoxysilane was added (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to γ-aminopropyltriethoxysilane was 1:0.05), the temperature was increased and maintained at 90°C for 3 hours, and after the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain a phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 3836 g / mol;
[0040] (3) After the phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 were mixed uniformly in a mass ratio of 3:2:3:0.1:100, a non-hydrolytic sol-gel reaction was carried out at a temperature of 90°C for 4 hours, and an in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0041] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 73.9 nm, the inner core diameter was 50.3 nm, and the outer shell thickness was 23.6 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 5.9%.
[0042] The structure of the phosphaphenanthrenesiloxane bio-based macromolecule synthesized in step (2) of Example 1 was characterized by nuclear magnetic resonance spectroscopy. Figure 1 , Figure 2 As shown. Among them, 1 The characterization results of H-NMR are as follows: the chemical shift between 6.9 and 8.0 ppm corresponds to the five proton characteristic peaks on the phosphaphenanthrene ring, the chemical shift between 5.1 and 5.3 ppm, δ=3.9 to 4.3 ppm corresponds to the proton characteristic peak on the middle carbon of the ester group in the epoxy soybean oil, the chemical shift between 3.8 and 3.6 ppm corresponds to the proton characteristic peak on the methylene next to the methyl in the silane coupling agent, the chemical shift between 2.8 and 3.1 ppm corresponds to the proton characteristic peak on the epoxy group, the chemical shift between 0.9 and 2.4 ppm corresponds to the proton characteristic peak on the fatty chain in the epoxy soybean oil, the chemical shift at 1.1 ppm corresponds to the proton characteristic peak on the methyl in the silane coupling agent, the chemical shift between 0.6 and 0.9 ppm corresponds to the proton characteristic peak on the methyl at the end of the chain, and the chemical shift between 0.5 and 0.6 ppm corresponds to the proton characteristic peak on the methylene next to silicon; 31 The P-NMR characterization results showed that there was only one peak of the P element in the phosphaphenanthrenesiloxane bio-based flame retardant branched macromolecule, and the chemical shift was located at 14.7 ppm.
[0043] The particle size distribution of the core-shell bio-based flame retardant nanoparticles of the in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material of Example 1 was tested by referring to the standard GB / T 29022 particle size analysis dynamic light scattering (DLS) particle size analysis. The results are as follows Figure 3 shown.
[0044] Example 2
[0045] The only difference between Example 2 and Example 1 is that in step (3), the mass ratio of phosphaphenanthrenesiloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 is 6:2:3:0.1:100.
[0046] The final in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material was prepared, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 81.4nm, the core diameter was 51.5nm, and the shell thickness was 29.9nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 7.9%.
[0047] Example 3
[0048] The only difference between Example 3 and Example 1 is that in step (3), the mass ratio of phosphaphenanthrenesiloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 is 9:2:3:0.1:100.
[0049] The final in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material was prepared. The average particle size of the core-shell bio-based flame retardant nanoparticles was 86.2 nm, the inner core diameter was 52.7 nm, and the outer shell thickness was 33.5 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 9.8%.
[0050] Example 4
[0051] The difference between Example 4 and Example 1 is that step (4) is: the core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and the polyetheramine (Huntsman D230) curing agent are mixed and stirred in a mass ratio of 100:29, and then vacuum degassed at 25°C for 2 minutes, poured into a silicone mold and cured under the conditions of 80°C / 2 hours + 110°C / 2 hours + 130°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles is 73.9 nm, the inner core diameter is 50.3 nm, and the outer shell thickness is 23.6 nm; the weight content of the core-shell bio-based flame retardant nanoparticles is 5.7%.
[0052] Example 5
[0053] (1) Under the protection of high-purity nitrogen, DOPO and epoxidized soybean oil ESO (the mass ratio of epoxidized soybean oil to DOPO was 1:1.2) were added to a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 150°C for 72 h to obtain a phosphaphenanthrene epoxidized soybean oil intermediate with an average epoxide value of 0.02 mol / 100 g.
[0054] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy soybean oil intermediate was dissolved in 1,4-dioxane (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to 1,4-dioxane was 1:5), γ-aminopropyltriethoxysilane was added (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to γ-aminopropyltriethoxysilane was 1:0.05), the temperature was increased and maintained at 90°C for 3 hours, and after the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain a phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 2316 g / mol;
[0055] (3) After the phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 were mixed uniformly in a mass ratio of 3:2:3:0.1:100, a non-hydrolytic sol-gel reaction was carried out at a temperature of 90°C for 4 hours, and an in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0056] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 91.3 nm, the inner core diameter was 63.5 nm, and the outer shell thickness was 27.8 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 5.9%.
[0057] Example 6
[0058] (1) Under the protection of high-purity nitrogen, DOPO and epoxidized soybean oil ESO (the mass ratio of epoxidized soybean oil to DOPO was 1:0.2) were added to a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 150°C for 72 hours to obtain a phosphaphenanthrene epoxidized soybean oil intermediate with an average epoxide value of 0.41 mol / 100 g.
[0059] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy soybean oil intermediate was dissolved in 1,4-dioxane (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to 1,4-dioxane was 1:5), γ-aminopropyltriethoxysilane was added (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to γ-aminopropyltriethoxysilane was 1:0.05), the temperature was increased and maintained at 90°C for 3 hours, and after the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain a phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 3532 g / mol;
[0060] (3) After the phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 were mixed uniformly in a mass ratio of 3:2:3:0.1:100, a non-hydrolytic sol-gel reaction was carried out at a temperature of 90°C for 4 hours, and an in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0061] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 73.1 nm, the inner core diameter was 50.7 nm, and the outer shell thickness was 22.4 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 5.9%.
[0062] Example 7
[0063] (1) Under the protection of high-purity nitrogen, DOPO and epoxidized soybean oil ESO (the mass ratio of epoxidized soybean oil to DOPO was 1:1) were added to a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 150°C for 72 hours to obtain a phosphaphenanthrene epoxidized soybean oil intermediate with an average epoxide value of 0.07 mol / 100 g.
[0064] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy soybean oil intermediate was dissolved in 1,4-dioxane (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to 1,4-dioxane was 1:5), γ-aminopropyltriethoxysilane was added (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to γ-aminopropyltriethoxysilane was 1:0.2), the temperature was increased and maintained at 90°C for 3 hours, and after the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain a phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 6714 g / mol;
[0065] (3) After the phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 were mixed uniformly in a mass ratio of 3:2:3:0.1:100, a non-hydrolytic sol-gel reaction was carried out at a temperature of 90°C for 4 hours, and an in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0066] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 95.1 nm, the inner core diameter was 53.4 nm, and the outer shell thickness was 41.7 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 5.9%.
[0067] Example 8
[0068] (1) Under the protection of high-purity nitrogen, DOPO and epoxidized soybean oil ESO (the mass ratio of epoxidized soybean oil to DOPO was 1:1) were added into a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 160°C for 72 h to obtain a phosphaphenanthrene epoxidized soybean oil intermediate with an average epoxide value of 0.07 mol / 100 g.
[0069] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy soybean oil intermediate was dissolved in 1,4-dioxane (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to 1,4-dioxane was 1:5), and triethoxypropyl isocyanate was added (the mass ratio of the phosphaphenanthrene epoxy soybean oil intermediate to triethoxypropyl isocyanate was 1:0.57). The temperature was raised and maintained at 30°C for 3 hours. After the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain a phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 2573 g / mol.
[0070] (3) Phosphaphenanthrene siloxane bio-based macromolecules, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 were mixed uniformly in a mass ratio of 2:2:3:0.1:100, and then subjected to a non-hydrolytic sol-gel reaction at 90°C for 5 h, and in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0071] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 71.9 nm, the inner core diameter was 51.6 nm, and the outer shell thickness was 20.3 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 5.2%.
[0072] The structure of the phosphaphenanthrenesiloxane bio-based macromolecule synthesized in step (2) of Example 8 was characterized by nuclear magnetic resonance spectroscopy. Figure 4 As shown. Among them, 1 The characterization results of H-NMR are as follows: the chemical shift between 6.9 and 8.0 ppm corresponds to the five characteristic peaks of protons on the phosphaphenanthrene ring, the chemical shift between 5.1 and 5.3 ppm and 3.9 and 4.3 ppm corresponds to the characteristic peak of protons on the middle carbon of the ester group in the epoxy soybean oil, the chemical shift between 3.7 and 3.4 ppm corresponds to the characteristic peak of protons on the methylene group next to the methyl group in the silane coupling agent, the chemical shift between 2.8 and 3.1 ppm corresponds to the characteristic peak of protons on the epoxy group, the chemical shift between 0.9 and 2.4 ppm corresponds to the characteristic peak of protons on the fatty chain in the epoxy soybean oil, the chemical shift between 1.2 and 1.5 ppm corresponds to the characteristic peak of protons on the methylene group between two carbons in the silane coupling agent, the chemical shift between 0.6 and 0.9 ppm corresponds to the characteristic peak of protons on the methyl group at the end of the chain, and the chemical shift between 0.5 and 0.6 ppm corresponds to the characteristic peak of protons on the methylene group next to silicon.
[0073] Example 9
[0074] The only difference between Example 9 and Example 8 is that in step (3), the mass ratio of phosphaphenanthrenesiloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 is 2:4:6:0.1:100.
[0075] The final in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material was prepared, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 87.2nm, the inner core diameter was 67.4nm, and the outer shell thickness was 19.8nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 8.5%.
[0076] Example 10
[0077] The only difference between Example 10 and Example 8 is that in step (3), the mass ratio of phosphaphenanthrenesiloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 is 2:6:9:0.3:100.
[0078] The final in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material was prepared, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 92.2nm, the core diameter was 71.6nm, and the shell thickness was 20.6nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 11.6%.
[0079] The cross-sectional microstructure of the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material of Example 10 was observed using a scanning electron microscope (the sample was subjected to gold spraying before testing). Figure 5 As shown, it can be seen that the nanoparticles can be evenly and stably dispersed in the composite material.
[0080] Embodiment 11
[0081] The difference between Example 11 and Example 8 is that step (4) is: the core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and the polyetheramine (Huntsman D230) curing agent are mixed and stirred in a mass ratio of 100:29, and then vacuum degassed at 25°C for 2 minutes, poured into a silicone mold and cured under the conditions of 80°C / 2 hours + 110°C / 2 hours + 130°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles is 71.9 nm, the inner core diameter is 51.6 nm, and the outer shell thickness is 20.3 nm; the weight content of the core-shell bio-based flame retardant nanoparticles is 5.1%.
[0082] Example 12
[0083] (1) Under the protection of high-purity nitrogen, DOPO and epoxy castor oil ECO (the mass ratio of epoxy castor oil to DOPO is 1:0.5) were added to a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 160°C for 50 h to obtain a phosphaphenanthrene epoxy castor oil intermediate with an average epoxy value of 0.23 mol / 100 g;
[0084] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy castor oil intermediate was dissolved in tetrahydrofuran (the mass ratio of the phosphaphenanthrene epoxy castor oil intermediate to tetrahydrofuran was 1:7), γ-aminopropyltrimethoxysilane was added (the mass ratio of the phosphaphenanthrene epoxy castor oil intermediate to γ-aminopropyltrimethoxysilane was 1:0.07), the temperature was increased and maintained at 90°C for 3 hours, and after the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain a phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 3536 g / mol;
[0085] (3) After the phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, barium hydroxide and bisphenol A epoxy resin E44 were uniformly mixed in a mass ratio of 3:2:3:0.1:100, a non-hydrolytic sol-gel reaction was carried out at a temperature of 100°C for 3 hours, and an in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0086] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed and stirred in a mass ratio of 100:21.5, and then vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 71.9 nm, the inner core diameter was 50.3 nm, and the outer shell thickness was 21.6 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 6.1%.
[0087] Embodiment 13
[0088] (1) Under the protection of high-purity nitrogen, DOPO and epoxy linseed oil ELO (the mass ratio of epoxy linseed oil to DOPO was 1:0.5) were added to a three-necked flask in sequence, and the temperature was raised to 120°C. After DOPO was completely melted, the temperature was raised and maintained at 140°C for 72 hours to obtain a phosphaphenanthrene epoxy linseed oil intermediate with an average epoxy value of 0.21 mol / 100 g.
[0089] (2) Under the protection of high-purity nitrogen, the phosphaphenanthrene epoxy linseed oil intermediate was dissolved in 1,4-dioxane (the mass ratio of the phosphaphenanthrene epoxy linseed oil intermediate to 1,4-dioxane was 1:5), N-β(aminoethyl)-γ-aminopropyltrimethoxysilane was added (the mass ratio of the phosphaphenanthrene epoxy linseed oil intermediate to N-β(aminoethyl)-γ-aminopropyltrimethoxysilane was 1:0.07), the temperature was raised and maintained at 90°C for 3 hours, after the reaction was completed, the solvent was removed and dried under vacuum conditions to obtain the phosphaphenanthrene siloxane bio-based macromolecule with an average molecular weight of 3263 g / mol;
[0090] (3) After the phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 were mixed uniformly in a mass ratio of 3:2:3:0.1:100, a non-hydrolytic sol-gel reaction was carried out at a temperature of 90°C for 4 hours, and an in-situ polycondensation was performed to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture;
[0091] (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 min. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 70.1 nm, the inner core diameter was 49.6 nm, and the outer shell thickness was 20.5 nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 5.9%.
[0092] Comparative Example 1
[0093] Bisphenol A epoxy resin E51 and 4,4-diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:25, stirred evenly, and vacuum degassed at 25°C for 2 minutes. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare a cured epoxy resin material.
[0094] Comparative Example 2:
[0095] Bisphenol A epoxy resin E51 and polyetheramine (Huntsman D230) curing agent were mixed in a mass ratio of 100:29, stirred evenly, and vacuum degassed at 25°C for 2 minutes. The mixture was poured into a silicone mold and cured at 80°C / 2 hours + 110°C / 2 hours + 130°C / 2 hours to prepare a cured epoxy resin material.
[0096] Comparative Example 3
[0097] Bisphenol A epoxy resin E44 and 4,4-diaminodiphenylmethane (DDM) curing agent were mixed in a mass ratio of 100:21.5, stirred evenly, and vacuum degassed at 25°C for 2 minutes. The mixture was poured into a silicone mold and cured at 100°C / 2 hours + 150°C / 2 hours + 180°C / 2 hours to prepare a cured epoxy resin material.
[0098] Comparative Example 4
[0099] The difference between Comparative Example 4 and Example 1 is that in step (3), the mass ratio of phosphaphenanthrenesiloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsiloxane, dibutyltin dilaurate and bisphenol A epoxy resin E51 is 18:6:9:0.3:100.
[0100] The final in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material was prepared, wherein the average particle size of the core-shell bio-based flame retardant nanoparticles was 127.3nm, the inner core diameter was 86.9nm, and the outer shell thickness was 40.4nm; the weight content of the core-shell bio-based flame retardant nanoparticles was 20.1%.
[0101] Related performance tests:
[0102] (1) Notched impact strength: Tested according to GB / T1843-1996 standard, the sample size is 80 mm × 10 mm × 4 mm, and the notched residual thickness is 8 mm.
[0103] (2) Limiting oxygen index: Tested in accordance with GB / T 2406-2009, sample size: 80 mm × 6.5 mm × 3 mm.
[0104] (3) Flame retardant grade: Refer to standard GB / T 2408-2008 to test UL94 vertical oxygen index, the sample size is 120 mm × 13 mm × 3 mm.
[0105] Table 1: Relevant performance test results of Examples 1-13 and Comparative Examples 1-4
[0106] .
[0107] It can be seen from the results of the above embodiments and comparative examples that the present invention in situ constructs core-shell bio-based flame retardant nanoparticles in the epoxy resin matrix so that the nanoparticles can be evenly and stably dispersed in the epoxy resin group, thereby obtaining an in situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material that has both excellent flame retardant properties and impact resistance.
Claims
1. A method for preparing an in-situ core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material, characterized in that: The following steps are involved: (1) The epoxy vegetable oil and DOPO are heated to 120-160°C under an inert gas atmosphere and reacted for 24-48 hours to synthesize a phosphaphenanthrene epoxy vegetable oil intermediate; wherein the mass ratio of the epoxy vegetable oil to DOPO is 1:(0.2-1.2); (2) dissolving the phosphaphenanthrene epoxy vegetable oil intermediate in an organic solvent, adding a silane coupling agent, reacting for 1-5 hours under the protection of an inert gas atmosphere, removing the solvent after the reaction is completed, drying, and obtaining a phosphaphenanthrene siloxane bio-based macromolecule; the silane coupling agent is selected from any one or more of an aminosilane coupling agent or an isocyanate silane coupling agent; when the silane coupling agent is selected from an aminosilane coupling agent, the mass ratio of the phosphaphenanthrene epoxy vegetable oil intermediate to the aminosilane coupling agent is 1:(0.05-0.5), and the reaction temperature is 80-100°C; when the silane coupling agent is selected from an isocyanate silane coupling agent, the mass ratio of the phosphaphenanthrene epoxy vegetable oil intermediate to the isocyanate silane coupling agent is 1:(0.2-0.6), and the reaction temperature is 0-100°C; (3) mixing phosphaphenanthrene siloxane bio-based macromolecule, trimethyloxyphenylsilane, dihydroxydiphenylsilane, initiator and epoxy resin in a mass ratio of (1-10):(1-10):(1.5-15):(0.01-0.15):100, performing a non-hydrolytic sol-gel reaction at a temperature of 80-100°C for 1-5h, and in-situ polycondensation to obtain a core-shell bio-based flame retardant nanoparticle / epoxy resin mixture; (4) The core-shell bio-based flame retardant nanoparticle / epoxy resin mixture and the curing agent are mixed in a mass ratio of 100:(20-50) and stirred evenly, and then vacuum degassed at 20-40°C, poured into a mold and cured to prepare an in-situ constructed core-shell bio-based flame retardant nanoparticle / epoxy resin composite material.
2. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The epoxidized vegetable oil is selected from any one or more of epoxidized soybean oil, epoxidized castor oil or epoxidized linseed oil.
3. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The aminosilane coupling agent is selected from any one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane or aminoethylaminoethylaminopropyltrimethoxysilane; the isocyanate silane coupling agent is selected from any one or more of isocyanatepropyltrimethoxysilane, isocyanatepropyltriethoxysilane, isocyanatepropylmethyldimethoxysilane or isocyanatepropylmethyldiethoxysilane.
4. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The average epoxide value of the phosphaphenanthrene epoxidized vegetable oil intermediate is 0.04 mol / 100g-0.42 mol / 100g.
5. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The average molecular weight of the phosphaphenanthrenesiloxane bio-based macromolecule is 1000-7500 g / mol.
6. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 5, characterized in that: The average molecular weight of the phosphaphenanthrenesiloxane bio-based flame retardant branched macromolecule is in the range of 1500-5500 g / mol.
7. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The inert gas is nitrogen, helium or argon; the organic solvent is selected from one or more of tetrahydrofuran, 1,4-dioxane, diethylene glycol dimethyl ether, chloroform, ethanol, petroleum ether or n-hexane.
8. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The epoxy resin is selected from any one or more of epoxy resin E51, epoxy resin E44, epoxy resin E42 or epoxy resin E31; the initiator is selected from any one or more of barium hydroxide or dibutyltin dilaurate.
9. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The curing agent is selected from any one or more of diaminodiphenylmethane, diaminodiphenylaldehyde, polyetheramine, amino-terminated trimethylolpropane tripropylene glycol ether, hexahydrophthalic anhydride or tetrahydrophthalic anhydride.
10. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The core-shell bio-based flame-retardant nanoparticles in the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material have an average particle size of 0.1nm-100nm, a core diameter of 10-100nm, and a shell thickness of ≤50nm.
11. The method for preparing the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material according to claim 1, characterized in that: The weight content of the core-shell bio-based flame-retardant nanoparticles in the in-situ constructed core-shell bio-based flame-retardant nanoparticle / epoxy resin composite material is 1%-20%.
Citation Information
Patent Citations
Polyhedral oligomeric silsesquioxane containing DOPO group and preparation method thereof
CN101787055A
Phosphor-nitrogen containing silane A, phosphite ester halogen-free flame retardant containing nitrogen phosphor silicon and preparation method of phosphite ester halogen-free flame retardant
CN103387589A